The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1159/000526098
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Liquid-Based Cytology Preservative Solutions and Artificial Intelligence: Liquid-Based Cytology Specimen Cell Detection Using YOLOv5 Deep Convolutional Neural Network

Abstract: <b><i>Introduction:</i></b> Deep learning is a subset of machine learning that has contributed to significant changes in feature extraction and image classification and is being actively researched and developed in the field of cytopathology. Liquid-based cytology (LBC) enables standardized cytological preparation and is also applied to artificial intelligence (AI) research, but cytological features differ depending on the LBC preservative solution types. In this study, the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The detection rate of TP preparations for the TS models was higher than that of the SP preparations in all five cell lines but was slightly lower than that of the TP model. This is consistent with our previous finding that the preparations used for training and detection should follow the same processing techniques to obtain a high detection rate with a high degree of accuracy 12. Although it may be possible to use a specific model based on the type of fixative, it is almost impossible to use a tumour-specific model for diagnostic samples.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…The detection rate of TP preparations for the TS models was higher than that of the SP preparations in all five cell lines but was slightly lower than that of the TP model. This is consistent with our previous finding that the preparations used for training and detection should follow the same processing techniques to obtain a high detection rate with a high degree of accuracy 12. Although it may be possible to use a specific model based on the type of fixative, it is almost impossible to use a tumour-specific model for diagnostic samples.…”
supporting
confidence: 89%
“…The detection rate (approximately 25%) varies depending on the type of LBC preservative solution used. 12 According to the reports, the TP and SP specimens have different morphologies. [6][7][8][9][10] Mathematical and statistical analyses have revealed that the cytoplasm and nuclear areas of the TP specimens were larger than those of the SP specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations